Pectin from Durian (Durio zibethinus Murray) Peel: Microwave-Assisted Extraction Followed by Solvent Extraction - Kheowmung, Wachiraporn (Trends in Sciences, 2024)
The world market demand for pectin has been growing fast due to the expanding consumer base for low-calorie and low-fat food products. Thus, there was a need to explore other sources of pectin. This study extracted pectin from durian (Durio zibethinus Murray) peel cv. Long lab-lae. Before solvent extraction, microwave-assisted extraction was utilized to improve the pectin yield. The parameters during the pectin extraction process were investigated using acetic acid concentrations ranging from 10 to 40 % at pH 2, extraction temperatures ranging from 40 to 100 °C, and extraction times ranging from 2 to 6 h. The pectin extraction was carried out at pH 2.0 because a higher pH significantly reduced the yield. The results showed the parameters had a significant influence on the yield. It decreased at a higher acid concentration, extraction temperature and extraction time. It was noticed that the pectin turned into liquid at a higher temperature, 100 °C. Therefore, the optimum conditions for extracting the highest yield of pectin were 20 % acetic acid, an extraction temperature of 80 °C, and an extraction time of 2 h. The pectin yield under these optimum conditions was 1.91 %. The Fourier transform infrared spectroscopy (FT-IR) analysis confirmed the presence of functional groups in the fingerprint region of identification for polysaccharides in the extracted pectin. The FT-IR spectrum of the pectin in durian peel was extremely close to that of commercial pectin. There was limited published data on extracting and characterizing pectin from durian peel. Thus, this study could pave the way for using durian peel pectin, for instance, in food processing (i.e., gelling agent for weak-acid, low-calorie food) and pharmaceutical applications. Furthermore, using durian peel, which is agricultural waste, reduces the disposal and burning of waste to the environment, causing several pollutions and improving the economic value of durian peel. HIGHLIGHTS Acetic acid concentration, extraction temperature and time impacted durian peel pectin yield Durian peel pectin yield was decreased at a higher acetic concentration, extraction temperature and time The optimum extraction conditions were 20 % acetic acid, 80 °C and 2 h FT-IR spectrum of the durian peel pectin was extremely close to that of commercial pectin GRAPHICAL ABSTRACT